2012
DOI: 10.1177/0363546512446591
|View full text |Cite
|
Sign up to set email alerts
|

The Western Ontario Rotator Cuff Index in Rotator Cuff Disease Patients

Abstract: Applied to a variety of RC patients, the WORC had high internal consistency, moderate to good construct validity, high test-retest reliability, and good responsiveness. These findings support the use of the WORC as a condition-specific self-reported outcome measure in RC patients, but its validity in patients with severe symptoms needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 51 publications
12
31
1
Order By: Relevance
“…The mean score of 29.4 (SD ± 13.8) in our study population indicated a more severe level of disability compared with these populations. The level of disability in our study population is comparable to other studies of patients with shoulder impingement syndrome [53,54]. …”
Section: Discussionsupporting
confidence: 88%
“…The mean score of 29.4 (SD ± 13.8) in our study population indicated a more severe level of disability compared with these populations. The level of disability in our study population is comparable to other studies of patients with shoulder impingement syndrome [53,54]. …”
Section: Discussionsupporting
confidence: 88%
“…The sample size is calculated to test the superiority of the PR protocol over the UC protocol in the assessment of change in the WORC physical symptoms subscale at week 12 (primary outcome) [75]. With 41 patients per group, the study will have 80% power assuming the expected group difference in the mean changes from baseline is 12 points, corresponding to the suggested minimum clinical relevant difference [47], the common standard deviation is 20 (0–100 scale) [75] and a significance level of 5%.…”
Section: Methodsmentioning
confidence: 99%
“…With 41 patients per group, the study will have 80% power assuming the expected group difference in the mean changes from baseline is 12 points, corresponding to the suggested minimum clinical relevant difference [47], the common standard deviation is 20 (0–100 scale) [75] and a significance level of 5%. With an expected dropout around 20% during the study we will randomize and allocate 100 patients (50 to each group); analyzing the intention to treat (ITT) population, which will give power of 85% to detect the aforementioned difference.…”
Section: Methodsmentioning
confidence: 99%
“…If a response is lacking in any subscale, the lost item score can be compensated for by the mean of the other items in the subscale. Nevertheless, losses of more than two items in a subscale cannot be compensated, they must be listed as incomplete [32]. …”
Section: Methodsmentioning
confidence: 99%